Occult Uterine Sarcoma and Leiomyosarcoma: Incidence of and Survival Associated With Morcellation. Issue 4 (April 2016) - Raine-Bennett, Tina; Tucker, Lue-Yen; Zaritsky, Eve; Littell, Ramey D.; Palen, Ted; Neugebauer, Romain; Axtell, Allison; Schultze, Peter M.; Kronbach, David W.; Embry-Schubert, Julia; Sundang, Alvina; Bischoff, Kimberly; et al.
Abstract : Obstet Gynecol Surv 2016;71(4):214–215 Uterine leiomyomas are the most common indication for hysterectomy in the United States.